Toxicity of extracts from municipal wastewater to early life stages of Japanese medaka (Oryzias latipes) to evaluate removals of micropollutants by wastewater treatment. (10th November 2017) - Maya, Nicholas; Crispo, Calvin; McFarland, Victoria; Nasuhoglu, Deniz; Isazadeh, Siavash; Yargeau, Viviane; Metcalfe, Chris D.
Abstract: Treatment of municipal wastewater reduces the concentrations of some pharmaceuticals and personal care products (PPCPs), hormones, and drugs of abuse. However, reduced concentrations of these micropollutants in wastewater may not correlate with reduced toxicity because transformations of micropollutants and/or the formation of disinfection by‐products may generate toxic compounds. In the present study, we prepared extracts by solid phase extraction of samples collected from wastewater treatment plants (WWTPs) at various stages of treatment and tested these extracts for toxicity to early life stages of Japanese medaka ( Oryzias latipes ). Toxicity data for extracts prepared from a WWTP with secondary treatment showed that the numbers of exposed embryos ( n  = 12 per treatment) that did not hatch increased from 1 of 12 for the treatment with untreated effluent to 5 of 12 for the treatment with final treated effluent. For extracts prepared from a WWTP with tertiary treatment, toxicity among exposed embryos ( n  = 12 per treatment) also increased with each step of wastewater treatment, as shown by mortalities of 2 of 12 and 8 of 12 in treatments with extracts from untreated and final treated effluent, respectively, as well as an increase in the numbers of embryos that did not hatch from 2 of 12 to 9 of 12 in treatments with untreated and final treated effluent, respectively. Ozonation of treated wastewater collected from a third WWTP caused a high incidence of delayed hatch in exposed embryos ( n  = 24 per treatment). However, hatching success and the numbers of developmental abnormalities in embryos from this ozonation treatment were not different from controls. The present study shows the value of including toxicity testing to assess the effectiveness of technologies for treatment of municipal wastewater. Environ Toxicol Chem 2018;37:136–144. © 2017 SETAC